Relations between second language proficiency and formant-defined vowel space - Mildner, Vesna (Array, 1999)
The aim of this study was to compare the vowel systems of Croatian and English in terms of their formant-defined vowel space, and to check for language proficiency effects in Croatian speakers of English as a foreign language. The proficiency of 20 male Croatian speakers of English was rated by 10 English language experts, and their production of 11 English vowels was acoustically analyzed for F1, F2, and duration. It was found that they group the English vowels according to Croatian vowel categories and that they place greater emphasis on duration differences between the tense /i, u/ and their lax counterparts than native English speakers. Proficiency effects were found only for some vowels, but not for duration.